2018
DOI: 10.1098/rsos.171418
|View full text |Cite
|
Sign up to set email alerts
|

Landslides and dam damage resulting from the Jiuzhaigou earthquake (8 August 2017), Sichuan, China

Abstract: At 21.19 on 8 August 2017, an Ms 7.0 earthquake struck the Jiuzhaigou scenic spot in northwestern Sichuan Province, China. The Jiuzhaigou earthquake is a strike-slip earthquake with a focal depth of 20 km at 33.20° N and 103.82° E, and was caused by two concealed faults. According to emergency investigations and remote sensing interpretations, the Jiuzhaigou earthquake triggered 1780 landslides, damaged one dam (Nuorilang Waterfall) and broke one dam (Huohua Lake). The landslides mainly occurred in the Rize Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…The present study observed that the triggering of the landslides is in direct correlation with the distance from the drainage valley Zhao et al 2018). Figure 9 shows that maximum numbers (303) of landslides have occurred within 200 m from the drainage valley beds; this zone covers the maximum landslide frequency rate (53.2%).…”
Section: Distance From the Drainage Linesmentioning
confidence: 51%
“…The present study observed that the triggering of the landslides is in direct correlation with the distance from the drainage valley Zhao et al 2018). Figure 9 shows that maximum numbers (303) of landslides have occurred within 200 m from the drainage valley beds; this zone covers the maximum landslide frequency rate (53.2%).…”
Section: Distance From the Drainage Linesmentioning
confidence: 51%
“…The occurrence of landslides is a consequence of geological, meteorological, anthropogenic and triggering factors, commonly referred to as landslide controlling factors (Bai et al, 2010). Standard guidelines for choosing the optimal landslide controlling factors are unavailable, but the scale of analysis, the nature of the study area, the data availability, and the quasi-empirical and statistical criterions in literature can be referenced (Romer and Ferentinou, 2016;Zhou et al, 2016). In this study, slope, aspect, elevation, lithology, distance from faults, distance from rivers, land use-land cover (LULC), normalized difference vegetation index (NDVI), and peak ground acceleration (PGA) were selected as the landslide controlling factors, as shown in Fig.…”
Section: Landslide Controlling Factorsmentioning
confidence: 99%
“…1), and this earthquake was caused by tectonic movement of an NW-SE-oriented leftlateral strike-slip fault (Wang et al, 2018a). Although intense rainfall was not observed after the earthquake, numerous landslides were triggered by strong seismic vibration of ground (Zhao et al, 2018). Many scenic spots in the Jiuzhaigou National Nature Reserve were destroyed; as presented in Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…With the rapid development of space technology and electronic information technology, remote sensing has been increasingly used in disaster emergency responses and rescues, with its advantages of rapid, macro, all-weather, and nearly all-day monitoring [5], and has become one of the most economical and effective solutions for landslide extraction [6]. It is of great significance to get information on a landslide situation as soon as possible, make a reasonable rescue plan, determine the potential hazards for key investigation, reasonably arrange the affected residents, and avoid secondary disasters [7].…”
Section: Introductionmentioning
confidence: 99%